Blue Cone Monochromacy: Visual Function and Efficacy Outcome Measures for Clinical Trials - Luo, Xunda (PLoS One, 2015)
BACKGROUND: Blue Cone Monochromacy (BCM) is an X-linked retinopathy caused by mutations in the OPN1LW / OPN1MW gene cluster, encoding long (L)- and middle (M)-wavelength sensitive cone opsins. Recent evidence shows sufficient structural integrity of cone photoreceptors in BCM to warrant consideration of a gene therapy approach to the disease. In the present study, the vision in BCM is examined, specifically seeking clinically-feasible outcomes for a future clinical trial. METHODS: BCM patients (n = 25, ages 5–72) were studied with kinetic and static chromatic perimetry, full-field sensitivity testing, and eye movement recordings. Vision at the fovea and parafovea was probed with chromatic microperimetry. RESULTS: Kinetic fields with a Goldmann size V target were generally full. Short-wavelength (S-) sensitive cone function was normal or near normal in most patients. Light-adapted perimetry results on conventional background lights were abnormally reduced; 600-nm stimuli were seen by rods whereas white stimuli were seen by both rods and S-cones. Under dark-adapted conditions, 500-nm stimuli were seen by rods in both BCM and normals. Spectral sensitivity functions in the superior retina showed retained rod and S-cone functions in BCM under dark-adapted and light-adapted conditions. In the fovea, normal subjects showed L/M-cone mediation using a 650-nm stimulus under dark-adapted conditions, whereas BCM patients had reduced sensitivity driven by rod vision. Full-field red stimuli on bright blue backgrounds were seen by L/M-cones in normal subjects whereas BCM patients had abnormally reduced and rod-mediated sensitivities. Fixation location could vary from fovea to parafovea. Chromatic microperimetry demonstrated a large loss of sensitivity to red stimuli presented on a cyan adapting background at the anatomical fovea and surrounding parafovea. CONCLUSIONS: BCM rods continue to signal vision under conditions normally associated with daylight vision. Localized and retina-wide outcome measures were examined to evaluate possible improvement of L/M-cone-based vision in a clinical trial.